ANALISIS KINERJA KEUANGAN UNTUK MENILAI KESEHATAN PERUSAHAAN FARMASI MILIK BUMN (STUDI KASUS PT INDOFARMA (PERSERO) TBK.) - Vina Anggita Sari; Mujino Mujino (FE Program Studi Manajemen, 2022)
This study aims to determine the financial performance of PT Indofarma (Persero) Tbk. the period 2014 - 2019 whether it is in good condition or not. The method of measuring performance is by assessing the level of health. Based on the Decree of the Minister of State-Owned Enterprises Number: KEP-100 / MBU / 2002 it is focused on the financial aspect, consisting of 8 indicators including; return on equity, return on investment, cash ratio, current ratio, collection periods, inventory turnover, total asset turnover, total equity to total assets. The results of 8 indicators for 2014 - 2019 fluctuated, in 2014 the total score was 37.5 in the BBB category, in 2015 the total score was 42 in the BBB category, in 2016 the total score was 32.5 in the BB category, in 2017 the total score was 32.5 in the BB category, in 2018 the total score was 34.5 in the BB category, and in 2019 the total score was 40.5 in the BBB category. With the results of this assessment, it can be concluded that for 2014-2019 the level of financial health of PT Indofarma (Persero) Tbk. Get the predicate less healthy, because the total score at 6 years <65.